Life Cycle and Techno-Economic Assessment Templates for Emerging Carbon Management Technologies - Faber, Grant; Mangin, Christophe; Sick, Volker (Frontiers in Sustainability, 2021)
Technologies that valorize carbon dioxide are becoming an increasingly relevant component of the portfolio of solutions necessary to mitigate and reverse climate change. Assessing the environmental and economic characteristics of these technologies early in their developmental trajectories can help technologists either efficiently accelerate emissions reductions and commercialization or realize potential infeasibility and direct resources toward better opportunities. To aid in such assessments, this article constructs a typology of carbon removal and utilization technologies and identifies specific pathways in need of early-stage life cycle assessment (LCA) and techno-economic assessment (TEA) templates. Based on published literature and project experience, example LCA and TEA templates are developed for high-priority pathways with relatively low technology readiness levels including direct air capture, chemical synthesis, algae products, carbonated concrete, and carbonated aggregates. The templates attempt to capture the most important elements of early-stage LCA and TEA in an easily understandable and usable manner that still allows for reliable, order-of-magnitude estimations and hotspot analysis. Opportunities for other practitioners to use and build upon the templates are also discussed.